2006
DOI: 10.1196/annals.1383.016
|View full text |Cite
|
Sign up to set email alerts
|

The Candidate Gene Approach to Susceptibility for Abdominal Aortic Aneurysm

Abstract: There are two approaches to gene discovery for diseases when genetic susceptibility has been implicated by clinical genetic or case-control studies: (1) genome-wide screening and (2) evaluation of candidate genes. Each has specific advantages and disadvantages. The principal advantage of genome-wide screening is that it is impeccably objective in as much as it proceeds without any presuppositions regarding the importance of specific pathobiological features of the disease process. The principal disadvantage is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Other investigators also showed interest in the major histocompatibility complex [19]. In addition, we found an identical amino acid substitution in the ferritin light chain gene in 2 of 19 AAA patients [14].…”
Section: Human Genetics Of Aaasupporting
confidence: 71%
See 2 more Smart Citations
“…Other investigators also showed interest in the major histocompatibility complex [19]. In addition, we found an identical amino acid substitution in the ferritin light chain gene in 2 of 19 AAA patients [14].…”
Section: Human Genetics Of Aaasupporting
confidence: 71%
“…Initial efforts to root the genetic hypothesis in a molecular basis involved the candidate gene approach [14]. Our first contribution implicated the TIMP-1 gene [15], which was subsequently confirmed by a larger study [16].…”
Section: Human Genetics Of Aaamentioning
confidence: 74%
See 1 more Smart Citation
“…Of the 15 full text studies that were evaluated, three studies were excluded. Tilson and Ro24 were omitted on the basis of very small sample size (n=6), and two studies were not of case-control design 25 26. One additional study was identified by hand-searching the reference lists of included studies 20.…”
Section: Resultsmentioning
confidence: 99%
“…These approaches have been greatly facilitated by the development of powerful array platforms which can investigate millions of SNPs within single biological specimens 163,166. Data from these studies highlight regions of the genome which may be linked to the aneurysm phenotype, with SNPs of loci present on chromosome 19 commonly associated with AAA susceptibility 124,167,168.…”
Section: 0 Future Prospects Of Aaa Diagnosis and Monitoringmentioning
confidence: 99%